2017
DOI: 10.1016/j.ymthe.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Vaccine Targeting Glypican-3 as a Treatment for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) has a high morbidity and mortality rate worldwide, with limited treatment options. Glypican-3 (GPC3) is a glycosylphosphatidylinositol-anchored glycoprotein that is overexpressed in most HCC tissues but not in normal tissues. GPC3-targeting antibody therapy shows limited response in a clinical trial due to the lack of a tumor-specific cytotoxic T lymphocyte (CTL) response. Here, in C57/B6 mice, we demonstrated that intravenous infusion of GPC3-coupled lymphocytes (LC/GPC3) elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…In mice the opposite is found, with the overexpression of GPC3 in the liver resulting in lower liver cell proliferation and a lack of correlation with HCC formation . The mouse HCC cell line Hepa1‐6 has been reported to express GPC3, but we found that this cell line was not sensitive to immunotoxin treatment (Supporting Fig. ).…”
Section: Discussionmentioning
confidence: 66%
“…In mice the opposite is found, with the overexpression of GPC3 in the liver resulting in lower liver cell proliferation and a lack of correlation with HCC formation . The mouse HCC cell line Hepa1‐6 has been reported to express GPC3, but we found that this cell line was not sensitive to immunotoxin treatment (Supporting Fig. ).…”
Section: Discussionmentioning
confidence: 66%
“…19 Antibodies against GPC3 and GPC3-peptide vaccines have been demonstrated to be safe and effective. 36,37 Presently, CAR-NK-92 against GPC3 especially killed GPC3 + HCC cells and did not harm GPC3 − normal hepatocellular cells, suggesting that GPC3 is a suitable target in CAR-NK therapy.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to confirming these established signaling interactions, our in silico screen suggests putative interactions which may provide novel therapeutic targets for GBM. Binding of GPC3 to IGF1R or CD81 is known to contribute to hepatocellular carcinoma development and invasiveness 41 ; immunotherapies targeting GPC3, which are showing promise in hepatocellular carcinoma, 42 , 43 may also benefit GBM patients. Our results also suggest AFDN/MLLT4 (adherens junction formation factor/myeloid/lymphoid or mixed-lineage leukemia) as a ligand activating ephrin receptor A7, which has been linked to adverse outcome in primary and recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%